2023
DOI: 10.1021/acscentsci.2c01317
|View full text |Cite
|
Sign up to set email alerts
|

Rational Chemical Design of Molecular Glue Degraders

Abstract: Targeted protein degradation with molecular glue degraders has arisen as a powerful therapeutic modality for eliminating classically undruggable disease-causing proteins through proteasomemediated degradation. However, we currently lack rational chemical design principles for converting protein-targeting ligands into molecular glue degraders. To overcome this challenge, we sought to identify a transposable chemical handle that would convert protein-targeting ligands into molecular degraders of their correspond… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
36
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 40 publications
1
36
0
Order By: Relevance
“…Examples of this approach include large-scale chemical biology programs and close investigation of unexplained target degradation in the patent literature. ,, These studies point to an emerging strategy for molecular glue development that depends on the chemical elaboration of an established ligand for a degradation target. One recent report has taken explicit advantage of this strategy …”
Section: Introductionmentioning
confidence: 99%
“…Examples of this approach include large-scale chemical biology programs and close investigation of unexplained target degradation in the patent literature. ,, These studies point to an emerging strategy for molecular glue development that depends on the chemical elaboration of an established ligand for a degradation target. One recent report has taken explicit advantage of this strategy …”
Section: Introductionmentioning
confidence: 99%
“…[37][38][39] To date, the majority of protein degradation strategies targeting HDACs has been focused on the design of PROTACs which will also be the focus of this review, however Toriki et al recently reported molecular glues targeting HDAC1 and HDAC3 for degradation. 40 PROTACs designed to degrade their target protein typically contain three components: a ligand to engage the protein of interest (POI), a ligand to initiate protein degradation (most commonly an E3-ligand), and a linker covalently bonding these Fig. 1 Top: Vorinostat, romidepsin, belinostat and panobinostat are drugs that inhibit the HDAC catalytic active site and are FDA approved.…”
Section: Protacs As Chemical Probesmentioning
confidence: 99%
“…37–39 To date, the majority of protein degradation strategies targeting HDACs has been focused on the design of PROTACs which will also be the focus of this review, however Toriki et al recently reported molecular glues targeting HDAC1 and HDAC3 for degradation. 40…”
Section: Protacs As Chemical Probesmentioning
confidence: 99%
“…Recently, the fusion of covalent and molecular glue drug discovery has yielded a new and promising alternative drug discovery approach. 1,12 Briefly, covalent molecular glues incorporate an electrophile that reacts with a nucleophilic amino acid on one of the protein partners. Covalent molecular glues EN450 (ref.…”
Section: Introductionmentioning
confidence: 99%